2006
DOI: 10.21273/hortsci.41.4.1062b
|View full text |Cite
|
Sign up to set email alerts
|

(128) Effect of 2,4-DP Concentration on Fruit Drop Control and Maturation of `Braeburn' Apples

Abstract: Apple fruit abscission shortly before harvest is a frequent, recurring problem, thereby reducing potential yield. The synthetic auxin 2 (2,4-dichlorophenoxy) propionic acid (2,4-DP) was evaluated for its effect on reducing fruit drop and influencing ripening of `Braeburn' apples, in the High Valley region of Río Negro, Argentina (38°56'S, 67°59'W). Thirteen-year-old apple trees grafted on MM 111 rootstock were sprayed on 4 Mar. 2005, at 162 days after full bloom (DAFB) with 2,4-DP at doses of 0.05% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This indicates that specific fruit growth curves are required according to particular cultivar, soil, climate and orchard (Ortega et al, 1998). Several factors affect final fruit size such as cell number, cell size, intercellular spaces and rate of cell division, time and severity of thinning, pruning, temperature, irrigation and light stress (Garriz et al, 1999(Garriz et al, , 2000(Garriz et al, , 2001(Garriz et al, , 2006(Garriz et al, , 2010. Kaack and Lindhard Pedersen (2010) showed that apple fruit diameter was significantly affected by two climate factors: 1) degree days and 2) evaporation potential.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that specific fruit growth curves are required according to particular cultivar, soil, climate and orchard (Ortega et al, 1998). Several factors affect final fruit size such as cell number, cell size, intercellular spaces and rate of cell division, time and severity of thinning, pruning, temperature, irrigation and light stress (Garriz et al, 1999(Garriz et al, , 2000(Garriz et al, , 2001(Garriz et al, , 2006(Garriz et al, , 2010. Kaack and Lindhard Pedersen (2010) showed that apple fruit diameter was significantly affected by two climate factors: 1) degree days and 2) evaporation potential.…”
Section: Introductionmentioning
confidence: 99%